Surface characterization of a glass fiber post after nonthermal plasma treatment with hexamethyldisiloxane - Batista, Victor Eduardo de Souza [UNESP]; Vechiato-Filho, Aljomar José; Cesar, Paulo Francisco; Goiato, Marcelo Coelho [UNESP]; Rangel, Elidiane Cipriano [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Verri, Fellippo Ramos [UNESP]; Barão, Valentim Adelino Ricardo; dos Santos, Daniela Micheline [UNESP] (My University, 2017)
Purpose: To characterize the surface of glass fiber posts (GFP) after different surface treatments and evaluate which method incorporates higher amounts of silicon (Si) particles, as well as to evaluate the bond strength at the post/ composite-cement interface with four different surface treatments of glass fiber posts luted with composite cement. Materials and Methods: Twelve glass fiber posts were obtained from the manufacturer. The posts were randomly distributed into four groups (n = 3): Co (control), no surface treatment; S, 70% alcohol and silane (60 s); HF + S, 10% hydrofluoric acid gel (60 s) and silane (60 s); NTP, nonthermal plasma of hexamethyldisiloxane (HMDSO) associated with argon (30 min). The surface of each GFP was characterized through scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Forty GFPs were randomly divided into 4 groups according the surface treatments (n = 10) and cemented with one composite cement (Rely X U200) into artificial canine teeth. The specimens were placed in a universal testing machine and subjected to tensile testing until failure occurred. Statistical analysis of the atomic percentage and bond strength was performed using ANOVA, followed by the post-hoc Tukey test (p = 0.05). Results: EDS graphics showed that the NTP group had a higher Si atomic percentage (at%) than the other groups (p < 0.001). The HF + S group had a higher Si at% than did the Co and S groups. SEM images illustrated that the surfaces of the GFPs were variously modified after different treatments. The NTP group incorporated higher Si levels on the GFP surface and yielded the highest bond strengths (p < 0.005) compared to the other tested groups. Conclusion: Treatment with HMDSO + Ar plasma (NTP) incorporated higher Si levels on the surface of the GFPs without inducing critical defects. NTP treatment promoted better bond strength results when compared to the other tested group when GFPs were cemented with composite cement.
Keywords: Dental prosthesis; plasma gas; Silanes